Feminine farm operational methods, involvement, hardships and sensitivity in farming systems analysis - VERMA, NISHA; SINGH, M P; NATH, AMIT; KASHYAP, POONAM; SINGH, S P; PANWAR, A S (The Indian Journal of Agricultural Sciences, 2020)
The present study has been conducted to identify the sensitivity in the pre-dominant farming systems of Western plain zone of Uttar Pradesh (WPZ) considering the importance of gender specific technologies much needed for better efficiency and productivity of farming systems. Four pre-dominant farming systems have been identified in WPZ of Uttar Pradesh with the highest area share (57.1%) and highest farmer distribution (62.9%) in FS1: Crop + Dairy (1C+1-2B). The highest net return was found in FS2: Crop + Horticulture (Fruits) + Dairy (2C+ 1-2 B), whereas the lowest net return was noticed in FS3: Crop + Horticulture (Vegetables) + Dairy (1C + 1B). Load carrying through head load was found extensively performed by the women of FS3 followed by FS4: Horticulture + Crop + Dairy (1C+1B) and FS2 respectively. Chopper (hand tool) for chaff cutting, winnowing through natural wind, power operated winnowing without safety gadgets was performed in FS4 (33%), FS3 (22.8%) and FS4 (17%) respectively by family female workers. Threshing through hand beating was maximally performed by FS2 (81%) as hired female labour. Work involvement in farming system studies shows that female workers (family and hired) of FS3 contributed maximum (44.7%) followed by FS1 (41.5%). Also, the women participation index on drudgery prone activities was found highest amongst female workers (family and hired) of FS3 (87.8%) followed by FS1 (83.21%). The results indicate that FS3 may be tagged as sensitive farming system with respect to maximum number of female headed households contributing maximum work and hardships followed by FS1.